Photoelectrochemical nitrate reduction to ammonia over BiVO4/2D macromolecular with extremely low energy consumption. (5th April 2023) - Bai, Yajie; Gao, Shuyu; Xie, Wanru; Fang, Zhenyuan; Bai, Hongye; Fan, Weiqiang
Abstract: Photoelectrochemical nitrate ions (NO3 − ) reduction reaction (PEC NITRR) to produce ammonia (NH3 ) at ambient conditions could not only solve the problem of NO3 − pollution, but also transform the NO3 − to hydrogen carrier (NH3 ). Herein, we introduced Cu 2+ by construction of BiVO4 /CuPc, effectively adsorbed target reactant NO3 − and further promote its effective conversion to NH3 . This unique catalyst structure leads to a desirable NH3 yield (rNH3 = 12.98 μg h −1 cm −2 ) and Faraday efficiency (FE = 20.36%) at 0.1 V vs. RHE. Therefore, this work provides a new perspective for establishing a low energy consumption PEC NITRR to achieve sustainable transformation of pollutants. Graphical abstract: BiVO4 /CuPc could adsorb NO3 − and activate N–O bond, contributing to the efficient conversion of NO3 − pollution to excellent hydrogen energy carrier. Image 1 Highlights: Nitrate is converted into ammonia as hydrogen energy carrier and zero carbon fuel. CuPc rich in active Cu sites was introduced on the BiVO4 photocathode. Extremely low energy consumption (0.1 V vs. RHE) from nitrate to ammonia. The NH3 yield of BiVO4 /CuPc was reaches 12.98 μg h −1 cm −2, which is 3 fold higher that of the original BiVO4 . This method of modifying photocathode materials by phthalocyanine shows great versatility and function.